Inside threat : a novel - Quirk, Matthew (William Morrow, an imprint of HarperCollins Publishers, 2023)
"An attack on the White House sends the President and his top aides to take shelter in a top secret government facility buried deep underground--but they soon discover the threat is locked inside with them"--